Preparation of reduced graphene oxide film by chemical and thermal reduction method targeted for energy harvesting: article - Ismail, Ili Nadia; Othman, Nur Hidayati (2017)
Graphene has sparked an intense interest in the energy field over the recent few years. A water flow over graphene has been proved that it can generate energy approximately ~175W/m2 due to the actively charged ions present in the water. In order to harvest the energy, a good quality of graphene film with high electrical conductivity is desired. In this work, two techniques were used to prepare reduced graphene oxide film. Characterization by X-Ray Diffractometer and Fourier Transform Infrared Spectrocopy, as well as electrical tests were done on the film to measure the ability of reduced graphene film to harvest energy. Thermal reduction at 700°C has shown the highest conductivity when compared to reduction done at 300°C and reduction by ascorbic acid. The conductivity obtained from thermal reduction at 700°C is relatively higher at 56.39 S/m followed by reduction with ascorbic acid at 46.87 S/m. Referring to the results obtained, it is proven that the conductivity increases significantly when the temperature increase, thus for that reason, the reduced graphene oxide by thermal reduction at higher temperature was suggested for energy harvesting purposes.